The effects of using Information & Communication Technology (ICT) on the Learning process of secondary-school students - Ghaznavi, Mohammad Reza; Irani, Yousef (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The purpose of this research was to evaluate the effects of ICT on Zahedan's secondary-school students. Materials and method: The method of doing the descriptive research was surveying and the statistical community was all Zahedan's secondary-school students with 8000 population. In the academic year of 2012; the statistical sample is 367 students who have been selected by clustering sampling method. In this research we have used two vehicles inducing method and researcher date has been analyzed in two levels: Descriptive level (by using the frequency distribution tables, frequency percentage and drawing charts) and deductive (the T- Test, variance analyzing, Chi Square).Results: The main findings are that using of ICT on increasing determination, resolving ability, curiousness, and educational success and totally on learning of secondary-school students has been effective in a high level and this effectiveness differs among males and females with different averages.Conclusion: Results indicated that Using ICT effects on increase in educational success of secondary-school students.